An Encore of the Greatest Show on Earth: Victorian Marvels and Monsters Revamped for the Postmillennial Times - Kérchy, Anna (Hungarian Journal of English and American Studies, 2021)
Book review:Davies, Helen. Neo-Victorian Freakery: The Cultural Afterlife of the Victorian Freak Show. New York: Palgrave Macmillan, 2015. 239 pages. ISBN 978-1-137-40255-4. Hb. $90.